Summary of Babylonian Civilization during the Kashi Period (1595-1157 BC) - میرزا, أحمد; عمر, کەیفی بیرداود (Sulaimani Journal for Humanities, 2019)
The (KASSITS) are one of the most important inhabitants of the Zagros Mountains, and they ruled Babylon for more than four centuries (1595-1157 BC), And they have been able to score great victories inside and outside of Babylon because of the tolerant policy with people inside and the peace agreements with strong neighboring forces. Although the Babylonian civilization was advanced, it witnessed more development in the era of (KASSITS), in all aspects of social, economic and religious, and also artistic and literary, and this is what made the memory of the Kashmiris remain immortal until now that is why the memory of the (KASSITS) remains immortal until now. The research consists of four topics, which discuss the scientific and religious beliefs, administrative, economic and technical aspects of the (KASSITS), with a summary of the research, introduction, summary, and list of sources and references.